(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Pediatric diseases present unique diagnostic challenges due to age-dependent symptom variability, limited verbal communication from patients, and the necessity of avoiding invasive procedures. Machine learning (ML) and deep learning (DL) technologies have increasingly demonstrated potential for transforming diagnostic